Postmodern politics: feminism, identity, and gender in Angela Carter’s ​the Magic Toyshop ​ , ​Nights at the Circus ​ , and other selected works - Flávia Forcatho (2019)
This thesis examines the fiction of Angela Carter,The Magic Toyshop ,Nights at the Circus and other selected works, to shed light on the relation between feminism and postmodernism in her writings. I compare a selection of fictional works by Carter in order to analyze the evolutionofherapproachtofeministtheory.IarguethataprogressiveenrichmentofCarter’s discussions of feminism and gender is verifiable, as well as her gradual transition into more postmodern theorization and aesthetics. For the analysis of identity in line with feminist and postmodern criticism, I rely mostly on Susan Stanford Friedman’s notion of identities as continually constructed, profoundly marked by temporal and spatial axes, and shaped by a number of constituents together with gender. In view of the growing number of critical readings of Carter that resort to Judith Butler’s theory of gender performativity, I seek to investigate not only the similarities between Carter and Butler but also their divergences. I contend that Carter’s and Butler’s conceptualizations of gender differ in the former’s stress on the sexed body as important for feminism, which is notable in Nights at the Circus .In this sense, Carter is better placed together with gender theorists who, unlike Butler, embrace levels of strategic gender essentialism as reaction to the advances of postmodern relativization. As to desire, I adopt a Lacanian perspective for The Magic Toyshop that reveals desire in the novel as culturally, rather than organically, experienced, and argue that Nights at the Circus challenges compulsory heterosexuality and reflects upon the possibility of more equal heterosexual relationships.